SYMBIOTIC EFFICIENCY OF INOCULATION WITH NITROGEN-FIXING BACTERIA AND ARBUSCULAR MYCORRHIZAL FUNGI IN Tachigali vulgaris SEEDLINGS - Juliana Müller Freire; Sérgio Miana de Faria; Jerri Edson Zilli; Orivaldo José Saggin Júnior; Isabel Silveira Camargo; Janaína Ribeiro Costa Rouws; Ederson da Conceição Jesus (Revista Árvore, 2020)
ABSTRACT The present study aimed to evaluate the effect of inoculation with nitrogen-fixing bacteria (NFB) and arbuscular mycorrhizal fungi (AMF) on the development of Tachigali vulgaris seedlings under nursery conditions. The seedlings were produced in 1 kg bags on a substrate of sand and vermiculite (1:1), following a completely randomized experimental design in a 3 (NFB) x 2 (with and without AMF) factorial scheme with 3 additional control treatments consisting of: seedlings inoculated only with AMF (mycorrhizal control), non-inoculated seedlings fertilized with N (nitrogenized control) and without N (absolute control). The following variables were evaluated: height, stem diameter (SD), shoot dry mass (SDM), root dry mass (RDM) and nodule dry mass (NDM), P accumulation in the shoot, and root mycorrhizal colonization (RMC). Efficiency and effectiveness were calculated to evaluate the plant response to double inoculation. The treatments showed a significant effect for all variables, except for mycorrhizal colonization, nodule number, and dry mass, with the nitrogen treatment having the highest growth values. Plants submitted to double inoculation showed a higher accumulation of dry matter, height and SD, reaching a 124% higher RDM regarding the absolute control, 90% more SDM, and 207% more NDM regarding the seedlings inoculated only with rhizobia. The positive effect of double inoculation occurred regardless of the strain used. The results indicate that the joint inoculation of NFB and AMF was beneficial for the species, promoting its growth.